Small Paroxysmal Nocturnal Hemoglobinuria Clones in Autoimmune Hemolytic Anemia: Clinical Implications and Different Cytokine Patterns in Positive and Negative Patients - Fattizzo, Bruno; Giannotta, Juri; Zaninoni, Anna; Kulasekararaj, Austin; Cro, Lilla; Barcellini, Wilma (Frontiers in Immunology, 2020)
Autoimmune hemolytic anemia (AIHA) is characterized by immune mediated erythrocytes destruction by autoantibodies with or without complement activation. Additional pathologic mechanisms include cellular cytotoxicity, cytokline dysregulation, and inadequate bone marrow compensation with fibrosis/dyserythropoiesis. The latter resembles that of bone marrow failures, namely aplastic anemia and myelodysplastic syndromes. Paroxysmal nocturnal hemoglobinuria (PNH) clones are increasingly recognized in bone marrow failure syndromes, and their selection and expansion are thought to be mediated by immune mechanisms. In this study, we aimed to evaluate the prevalence of PNH clones in 99 patients with primary AIHA, and their correlations with disease features and outcomes. Moreover, in the attempt to disclose the physiopathology of PNH positivity in AIHA, serum levels of several immunomodulatory cytokines were tested. A PNH clone was found in 37 AIHA patients (37,4%), with a median size of 0.2% on granulocytes (range 0.03-85). Two patients showed a large clone (16 and 85%) and were therefore considered as AIHA/PNH association and not included in further analysis. Compared to PNH negative, PNH positive cases displayed a higher hemolytic pattern with adequate bone marrow compensation. AIHA type, response to therapy, complications and outcome were comparable between the two groups. Regarding cytokine levels, IFN-gamma and IL-17 were lower in PNH positive versus PNH negative AIHAs (0.3+0.2 vs 1.33+2.5; 0.15+0.3 vs 3,7+9.1, respectively, p=0.07 for both). In PNH positive AIHAs, IFN-gamma positively correlated with reticulocytes (r=0.52, p=0.01) and with the bone marrow responsiveness index (r=0.69, p=0.002). Conversely, IL-6 and IL-10 showed the same pattern in PNH positive and PNH negative AIHAs. IL-6 levels and TGF-beta positively correlated with clone size (r=0.35, p=0.007 and r=0.38, p=0.05, respectively), as well as with LDH values (r=0.69, p=0.0003 and r=0.34, p=0.07, respectively). These data suggest testing PNH clones in AIHA since their prevalence is not negligible, and may correlate with a prominent hemolytic pattern, a higher thrombotic risk, and a different therapy indication. PNH testing is particularly advisable in complex cases with inadequate response to AIHA-specific therapy. Cytokine patterns of PNH positive and negative AIHAs may give hints about the pathogenesis of highly hemolytic AIHA.